Periode Pemijahan Spons Aaptos aaptos (Porifera: Demospongia) di Perairan Pulau Pari, Kepulauan Seribu, DKI Jakarta - Kawaroe, Mujizat; Soedharma, Dedi; Siregar, Rahmadsyah Deny (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2008)
The purpose of this research was to study spawning period of sponge Aaptos aaptosat Pari Island, Thousand Islands, DKI Jakarta. The result showed that spawningtime occurred at 17.00-18.00, and within that time the sponge closed their osculumto throw out the zygote leaving the body faster. The duration of spawning rangefrom 4 minutes to 41 minutes. Based on the lunar periode, spawning for spongeAaptos aaptos started from early new moon till few days after full moon. Spawningmostly took place during spring tides. Based on the PCA analysis, it was found thatwater temperature and pressure had strong correlation with spawning time.